Discovery of Elusive K4O6, a Compound Stabilized by Configurational Entropy of Polarons. Issue 1 (26th November 2018) - Freysoldt, Christoph; Merz, Patrick; Schmidt, Marcus; Mohitkar, Shrikant; Felser, Claudia; Neugebauer, Jörg; Jansen, Martin
Abstract: Synthesis of elusive K4 O6 has disclosed implications of crucial relevance for new solid materials discovery. K4 O6 forms in equilibrium from K2 O2 and KO2, in an all‐solid state, endothermic reaction at elevated temperature, undergoing back reaction upon cooling to ambient conditions. This tells that the compound is stabilized by entropy alone. Analyzing possible entropic contributions reveals that the configurational entropy of "localized" electrons, i.e., of polaronic quasi‐particles, provides the essential contribution to the stabilization. We corroborate this assumption by measuring the relevant heats of transformation and tracking the origin of entropy of formation computationally. These findings challenge current experimental and computational approaches towards exploring chemical systems for new materials by searching the potential energy landscape: one would fail in detecting candidates that are crucially stabilized by the configurational entropy of localized polarons. Abstract : Configurational entropy of polarons crucially stabilizes hitherto elusive K4 O6 ; it forms in equilibrium while heating as illustrated by photos (a)–(c), and decays on cooling, (c)–(e). This unique finding, which has far reaching consequences for solid materials discovery in general, has been backed by quantitative experimental data and computational analyses, including a new approach to treating electron correlations in molecular π* orbitals.